2016
DOI: 10.1186/s13018-016-0344-7
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the InterTan nail and proximal femoral nail anti-rotation-Asia in the treatment of unstable intertrochanteric femur fractures in the elderly

Abstract: BackgroundThe purpose of this study was to compare the clinical outcomes of elderly patients undergoing surgery for treatment of unstable trochanteric fractures receiving either proximal femoral nails anti-rotation-Asia (PFNA-IIs) or InterTan nails (ITs).MethodsBetween January 1, 2012, and June 31, 2015, 168 elderly patients with unstable intertrochanteric femur fractures enrolled in this study. The only intervention was ITs or PFNA-IIs of the unstable trochanteric femur fractures. Follow-up was at 1, 3, 6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 34 publications
5
71
1
2
Order By: Relevance
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
“…These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes. Of these, two studies reported that there was no significant difference in the operative time between the InterTan intramedullary nail (IT) group and the GN or PFNA group [15, 20].…”
Section: Discussionmentioning
confidence: 91%
“…We got satisfactory results with PFNA-2, and there was no considerable difference between 2 groups in terms of functional outcome. e varus collapse was seen in 12% [18], 5.8% [21], and 4.9% [22] of cases in previous studies. We got 15% cases with varus collapse with screw back out in the lateral entry group.…”
Section: Advances In Orthopedicsmentioning
confidence: 57%
“…Though the overall complication rate was 20% but implant failure rate was only 2.8% no cut out has been reported. Yu et al [33] in their study reported combined implant failure cut-out in 9.7 of their cases. Implant failure rate is relatively lower in cephalomedullary nails with helical blade fixation technique.…”
Section: Discussionmentioning
confidence: 91%
“…This needs early mobilization to prevent medical co-morbidies and regain preinjury activity operative management have become preferred [5] . Implants should be used which have characteristics of less invasion, allow early weight bear and have less complication [6,7] .…”
Section: Introductionmentioning
confidence: 99%